Coconut and Its Derivatives: Sustainable Solutions for Health, Industry, and the Environment - Nur Aifiah Binti Ibrahim Ibrahim (CV. Eureka Murakabi Abadi, 2026)
Coconut oil is an extract derived from coconut phytochemicals and is widely used for energy production and various industrial applications. It contains a high level of nutrients and bioactive compounds that contribute to its value in health and medical care, particularly due to its cleansing and therapeutic properties. When processed from the coconut husk, the biocompound can be utilized as a fuel source, generating heat through controlled combustion. The physical structure of the husk, typically spherical or oblong, allows for efficient use in water-based and shell-supported applications. In addition to its functional uses, coconut products provide significant economic value, as they are appreciated for both their commercial potential and their role in reducing exposure to carcinogens and other harmful substances. Consequently, coconut oil and its derivatives are considered beneficial resources for industrial, medical, and environmental applications.